Assessing Service Quality in Yemeni Public Schools: A SERVQUAL Analysis of Teacher Perceptions - Mohammed Ali, Suaad Yahya; Amzat, Ismail Hussein (IIUM Journal of Educational Studies, 2026)
This study assesses service quality in Yemeni public schools by analyzing teacher perceptions through the SERVQUAL framework. It addresses a significant gap in the literature, as existing research on Yemen’s conflict-affected education system focuses primarily on structural damages and enrolment challenges, neglecting systematic measurement of day-to-day service quality from teachers’ operational perspectives. Employing a quantitative cross-sectional design, data was collected from 559 teachers across three strategically selected governorates of Sana’a, Aden, and Taiz using stratified random sampling. A validated, contextually adapted Arabic SERVQUAL questionnaire measured the five core dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Descriptive statistics and analysis of variance (ANOVA) were employed to analyze the data. Results revealed consistently low to moderate perceptions across all service quality dimensions, with a mean range of 2.39 to 2.61 on a 5-point scale. The dimension of empathy received the most favorable evaluations (M = 2.61), while tangibles were perceived as the most deficient (M = 2.39). ANOVA results demonstrated a statistically significant main effect of school level on service quality perceptions, F(9, 548) = 6.074, p < .001. Post-hoc tests revealed that teachers in Basic Education (Grades 1–9) reported significantly lower perceptions of service quality than those in Secondary Education (Grades 10–12), with a mean difference of -16.88, p = .002. However, the overall model explained a modest portion of the variance (R² = .091). These findings highlight systematic service delivery failures extending beyond resource scarcity to encompass administrative and relational gaps, with notable inequities between educational stages. The study concludes that targeted, multidimensional interventions prioritizing infrastructure rehabilitation alongside administrative process improvements, with a specific focus on basic education, are urgently needed to support sustainable educational recovery in Yemen’s protracted humanitarian crisis.